2021
DOI: 10.1177/09612033211061482
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of tRNA-derived small RNAs and their potential roles in lupus nephritis

Abstract: Objective Lupus nephritis (LN) is a major end-organ complication of systemic lupus erythematosus (SLE), and the molecular mechanism of LN is not completely clear. Accumulating pieces of evidence indicate the potential vital role of tRNA-derived small RNAs (tsRNAs) in human diseases. Current study aimed to investigate the potential roles of tsRNAs in LN. Methods We herein employed high‐throughput sequencing to screen the expression profiles of tsRNAs in renal tissues of the LN and control groups. To validate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…32,33 Yan Liang et al found that tRNA-derived small RNAs might contribute to the pathogenesis of lupus nephritis via the PI3K/AKT pathway. 34 Here, we discovered that downregulating miR-99a-3p expression in BALL-1 cells greatly enhanced the PI3K/AKT pathway activation, whereas downregulating NCAPG expression could inhibit the phosphorylation of PI3K and AKT. Also, we found that LY294002 partially blocked the effects of the miR-99a-3p antagonist on BALL-1 cell proliferation, apoptosis, and the cell cycle transition.…”
Section: Discussionmentioning
confidence: 85%
“…32,33 Yan Liang et al found that tRNA-derived small RNAs might contribute to the pathogenesis of lupus nephritis via the PI3K/AKT pathway. 34 Here, we discovered that downregulating miR-99a-3p expression in BALL-1 cells greatly enhanced the PI3K/AKT pathway activation, whereas downregulating NCAPG expression could inhibit the phosphorylation of PI3K and AKT. Also, we found that LY294002 partially blocked the effects of the miR-99a-3p antagonist on BALL-1 cell proliferation, apoptosis, and the cell cycle transition.…”
Section: Discussionmentioning
confidence: 85%
“…A total of 160 tsRNAs were identified by high-throughput sequencing in LN renal tissue, of which 79 were upregulated and 81 were downregulated. Bioinformatics analysis predicts that tsRNAs may play a role in the pathogenesis of LN through cell adhesion molecules as well as the B-cell receptor, PI3K-AKT, and MAPK signaling pathways ( 111 ). A total of 101 tRNAs and 355 tsRNAs were differentially expressed in PBMCs of SLE patients.…”
Section: Candidate Rnas As Sle Biomarkersmentioning
confidence: 99%
“…Mounting evidence has indicated that the aberrated expression of tsRNAs are deeply implicated in cancer, parasitic disease (12)(13)(14)(15)(16). Recently, a few studies including our previous research pay attention to the relationship between SLE and tsRNA (14,(17)(18)(19). However, the diagnostic values and biological functions of tsRNAs in urinary exosome, especially for LN, are still ambiguous and intriguing.…”
Section: Introductionmentioning
confidence: 99%